Neurofunctional topography of the human hippocampus. Issue 12 (9th September 2015) - Robinson, Jennifer L.; Barron, Daniel S.; Kirby, Lauren A. J.; Bottenhorn, Katherine L.; Hill, Ashley C.; Murphy, Jerry E.; Katz, Jeffrey S.; Salibi, Nouha; Eickhoff, Simon B.; Fox, Peter T.
Abstract: Much of what was assumed about the functional topography of the hippocampus was derived from a single case study over half a century ago. Given advances in the imaging sciences, a new era of discovery is underway, with potential to transform the understanding of healthy processing as well as the ability to treat disorders. Coactivation‐based parcellation, a meta‐analytic approach, and ultra‐high field, high‐resolution functional and structural neuroimaging to characterize the neurofunctional topography of the hippocampus was employed. Data revealed strong support for an evolutionarily preserved topography along the long‐axis. Specifically, the left hippocampus was segmented into three distinct clusters: an emotional processing cluster supported by structural and functional connectivity to the amygdala and parahippocampal gyrus, a cognitive operations cluster, with functional connectivity to the anterior cingulate and inferior frontal gyrus, and a posterior perceptual cluster with distinct structural connectivity patterns to the occipital lobe coupled with functional connectivity to the precuneus and angular gyrus. The right hippocampal segmentation was more ambiguous, with plausible 2‐ and 5‐cluster solutions. Segmentations shared connectivity with brain regions known to support the correlated processes. This represented the first neurofunctional topographic model of the hippocampus using a robust, bias‐free, multimodal approach. Hum Brain Mapp 36:5018–5037, 2015 . © 2015 Wiley Periodicals, Inc.